Efficient radar detection of weak manoeuvring targets using a coarse‐to‐fine strategy - Shengheng Liu; Hongchi Zhang; Tao Shan; Yongming Huang (IET Radar, Sonar & Navigation, 2021)
Abstract Detection of weak manoeuvring targets has always been an important yet challenging task for radar signal processing. One primary reason is that target variable motions within a coherent processing interval generate energy migrations across multiple resolution bins, which severely deteriorate the parameter estimation performance. The problem is compounded by an increasingly complex surveillance environment, as well as more affordable and pervasive than ever small targets such as drones. In this work, a coarse‐to‐fine strategy for the detection of weak manoeuvring targets is designed. First, a coarse estimation of the chirp parameter in an extended unambiguous range using a novel coprime segmented discrete polynomial‐phase transform is coherently integrated and derived. Sparse fractional Fourier transform is then employed to refine the coarse estimation at a significantly reduced computational complexity. The proposed scheme achieves an efficient and reliable weak target detection, while requires no a priori knowledge on the motion parameters, which is verified by the simulation results.